Gambaran perilaku ibu tentang kesehatan gigi dan mulut di sekolah dasar kota palembang - Dewi, Cristina; asia, Asyurati (Fakultas Kedokteran Gigi Universitas Trisakti, 2022)
Background: Dental and oral health is an important thing that must be maintained and cared for as best as possible to avoid the occurrence of diseases in the oral cavity. Knowledge of dental and oral health is very important in supporting behavior to maintain cleanliness and dental and oral health. Mother's knowledge can influence the formation of hygiene and oral health behavior in children, because mothers are people who are very close to children during their growth period and are role models for children. High knowledge will greatly impact a person's behavior in maintaining dental and oral health. Objective: To describe the overview of behavior of mother parents of primary school student about dental and oral health at the Karya Dharma Bhakti II Primary School in Palembang city. Methods: This type of research is descriptive observational research with a cross-sectional design or research design. The sample of this study were all mothers who had children at the Karya Dharma Bhakti II Primary School in Palembang city. This study uses a consecutive sampling technique, a minimum sample of 100 respondents. The data generated from the questionnaire will be collected and processed in the form of a frequency distribution table. Results: Respondents' knowledge of dental and oral health as many as 179 respondents (64%) in good category, attitudes as many as 158 respondents (57%) in good category, and actions as many as 206 respondents (74%) in good category so that the behavior of 234 respondents (84%) in good category. Conclusion: This study shows that the overview of behavior of mother parents of primary school student about dental and oral health at the Karya Dharma Bhakti II Primary School in Palembang city has a good category.